SUN’IY INTELLEKT TEXNOLOGIYALARI YORDAMIDA OLIY TA’LIMDA MASOFAVIY O‘QITISH TIZIMINI RIVOJLANTIRISH IMKONIYATLARI - Atabaeva, B.J. (SCIENCE and SOCIETY, 2024)
This article will analyze the experience of using e-learning in the world's leading higher education institutions and the methods of e-learning used in Uzbekistan. The technologies for creating electronic educational resources and their study in the improvement of educational processes are presented.
Keywords: artificial intelligence; distance learning; higher education; personalized education; automated assessment; virtual assistants; student support; educational technologies; adaptive education systems